Transportation and the Environment : A Review of Empirical Literature - Li, Shanjun; Xing, Jianwei; Yang, Lin; Zhang, Fan (World Bank, Washington, DC, 2020)
In urban areas around the world, increasing motorization and growing travel demand make the urban transportation sector an ever-greater contributor to local air pollution and greenhouse gas emissions. The situation is particularly acute in developing countries, where growing metropolitan regions suffer some of the world’s highest levels of air pollution. Policies that seek to develop and manage this transportation sector—to meet rising demand linked to economic growth and safeguard the environment and human health—have had strikingly different results, with some inadvertently exacerbating the traffic and pollution they seek to mitigate. This paper provides an overview of the findings of the recent literature on the impacts of a host of urban transportation policies used in developed and developing country settings. The paper identifies research challenges and future areas of study of transportation policies, which can have important, long-lasting impacts on urban life and global climate change.